Follicular Thyroid Carcinoma Metastatic to the Kidney: Report of a Case with Cytohistologic Correlation. (13th October 2015) - Nath, Vikas; Baliga, Mithra; Lewin, Jack; Souza, Frederico; Akhtar, Israh
Abstract : Here we report a case of a 45-year-old female who underwent thyroidectomy for thyroid cancer and presented 20 years later with a left renal mass. CT-guided core biopsy was performed, and imprints and histologic sections of the biopsy showed cells resembling thyroid follicular cells with a background containing colloid. Immunohistochemistry revealed positivity for thyroglobulin and thyroid transcription factor 1, consistent with metastatic follicular thyroid carcinoma (FTC). The patient later underwent radical nephrectomy; histologic sections of the resected tumor revealed an encapsulated lesion morphologically similar to the biopsy specimen. Thyroid metastases to the kidney are extremely rare and are often detected during postthyroidectomy surveillance by elevation in thyroid hormone levels, 131 I scintigraphy, or 18 F-fluorodeoxyglucose uptake in positron emission tomography studies. Treatment involves total thyroidectomy, resection of the metastatic foci, and 131 I therapy. The differential diagnoses of renal metastasis of FTC include the encapsulated follicular variant of papillary thyroid carcinoma (PTC), which possesses some of the nuclear features seen in conventional PTC but may occasionally be indistinguishable from FTC in cytologic preparations, and renal lesions such as benign thyroidization of the kidney and thyroid-like follicular carcinoma of the kidney, which mimic FTC in histologic appearance but do not stain with thyroid markers.